A systematic review of immunosuppressant adherence interventions in transplant recipients: Decoding the streetlight effect. (7th December 2017) - Duncan, S.; Annunziato, R. A.; Dunphy, C.; LaPointe Rudow, D.; Shneider, B. L.; Shemesh, E.
Abstract: Non‐adherence to immunosuppressant medications is an important risk factor for graft dysfunction. To evaluate the effectiveness of adherence‐enhancing interventions, we reviewed adherence intervention studies in solid organ transplant recipients (all ages). Using the following databases: PsycINFO, PubMed, Scopus, and ScienceDirect, we identified 41 eligible studies. Only three non‐randomized trials showed a possible positive effect on objective indicators of transplant outcomes (such as rejection, liver enzyme levels, kidney function). None of the 21 RCTs showed an improvement in transplant outcomes. Three studies showed a higher rate of adverse events in the intervention group as compared with controls, although this may be related to ascertainment bias. Improvement in adherence as measured indirectly (eg, with electronic monitoring devices) was not aligned with effects on transplant outcomes. We conclude that adherence interventions, to date, have largely been ineffective in improving transplant outcomes. To improve this track record, intervention efforts may wish to concentrate on non‐adherent patients (rather than use convenience sampling, which excludes many of the patients who need the intervention), use direct measures of adherence to guide the interventions, and employ strategies that are intensive and yet engaging enough to ensure that non‐adherent patients are able to participate.